Transhumanism and Religion in the Context of Digital Modernism: A Sociological Analysis - Ahmedi, Ekber Sah (Afyon Kocatepe Univ, 2024)
It can be said that one of the most important events in human history is the Industrial Revolution. This is because the Industrial Revolution has changed the way people organize, communicate and produce, in short, their entire way of life. In other words, it can be argued that the exponential progress of the revolution not only led to a transformation in political, economic, sociocultural, intellectual, and religious terms, but also made it possible to establish a digital world as an alternative to the physical world through the computerization and digitalization processes. Technological developments have increased the capability of the fields of biology and medicine and strengthened the idea of transhumanism, which points beyond the biological human being, such as increasing human capacity, extending life and even immortality. Transhumanism can be defined as a movement that seeks to remove the 'problems' such as disease, pain, and poverty through technological advancements. It aims to enhance human beings both physically and cognitively by overcoming the limits and restrictions imposed by their biological nature, and promises a cyber life that leads to immortality. Since transhumanism has a philosophy that encompasses all areas of the modern individual's life, it can be asserted that it is not only a movement, but also a philosophy of life, lifestyle, ideology, thought system, new age belief, new religious movement, and a religion in the sociological sense. The present study deals with transhumanism within the framework of digital modernity. Digital modernism, which is built on Web 2.0 technology and accepted as the new phase of modernism, claims that postmodernism is left behind and points to the digitalization of the text, the meeting of
Keywords: History; Age